Bidirectional DC–DC Converter with Coupled Inductor Fordc-Bus Regulation in Microgrid Applications - Mayer, Robson; Kattel , Menaouar Berrehil El; Oliveira, Sérgio Vidal Garcia (Eletrônica de Potência, 2020)
This paper presents a theoretical analysis and the experimental results of the bidirectional coupled inductor dc-dc converter for dc-bus voltage regulation and power compensation in dc-microgrid applications. In dc-microgrids, a power distribution system requires a bidirectional converter to control the power flow between dc-bus and batteries. Furthermore, the dc-bus needs to be kept stabilized within certain limits and the converter handles a large range of voltage variation in the accumulators. The proposed topology is also relatively feasible for low-input-voltage applications for interfacing energy storage elements, such as batteries, ultracapacitors with the high voltage dc-bus in electric vehicles. The converter allows greater voltage gain compared to classic non-isolated topologies and can better deal with the wide range of voltage variation imposed by the source/load. The operation principles, the DC voltage gain, the design of the filters, the voltage/current stresses and a comparison are discussed. The experimental results confirmed and validated the theoretical study as well as the converter performance so that the measurements performed obtained from a 600 W laboratory prototype.